Professional personality characteristics of manager nurses - Ülkü Baykal; Serap Sökmen; Arzu Kader Harmancı Seren (Association of Nurse Managers, 2018)
INTRODUCTION: This descriptive study was conducted the aim of defining the professional personality characteristics of nurse managers and demonstrating the relationship between these characteristics and personal/occupational variables. METHODS: The research was carried out in the sample of 500 executive nurses working in 20 hospitals in Istanbul and the data of 349 administrators were used. A survey aimed defining personal/occupational characteristics of manger nurses and Occupational Personality Questionnaire (OPQ-4.2) were used as data collection tools in the research. The analysis of the inventory was carried out by Saville & Holdsworth-Turkey. The analysis of the study was made by the statistical experts using percentage, t test, ANOVA, Tukey Post Hoc tests as further analysis. RESULTS: It has been determined that nurse managers are mostly in the age group of 31-40 years old with 10-14 years of professional experience and managerial experience of under 4 years. They are mostly single and lower level manager, with middle income and associate degree education. It was found that the manager nurses generally got average scores from the OPQ inventory and the distribution of scores changed between 4.04 and 6.51 in the 10 point system. When inventory scores of manager nurses were compared according to independent variables; there were significant differences in some personality dimensions according to the institution, age, education, professional experience, marital status and income status; it is determined that there is no difference in comparison with management experience. DISCUSSION AND CONCLUSION: It was determined that managerial personality characteristics of nurse managers were distributed within average limits and according to the personal and professional characteristics except managerial experience, significant differences were found. It may be recommended to conduct particularly qualitative research in this regard and to take account of professional personality characteristics in managerial appointments.